ANTIOXIDANT EFFECT OF PHYTOREMEDY “POLYNOOPHYT” - M. Yu. Itygilov; A. A. Toropova; Ya. G. Razuvayeva; S. A. Chukayev (Acta Biomedica Scientifica, 2012)
70 white rats (Wistar) of both sexes with the initial body weight 160-180g were used in the carried out research. It is defined, that the phytoremedy "Polynoophyt" has antioxidant effect in narcosis of natrium thiopental. It is established, that the phytoremedy "Polynoophyt" inhibits lipid peroxidation and. activates antioxidative system, of body in serum and brain homogenate in narcosis of natrium thiopental.